A new instrument for punch analysis in boxing - Chadli, S.; Ababou, N.; Ababou, A. (Procedia Engineering, 2014)
In boxing, evaluation of punch forces correlated with strikes frequencies and reaction time may give suitable information for intrinsic performance of athletes. Such information can be used for the follow-up of physical and technical preparation, for elaboration of selection criteria as well as for the young talent detection. We have developed a new device, able to quantify the athlete's reaction time, the force of punches and the frequency of series of strikes on height adjustable impact target. The device's concept, design, construction, calibration and preliminary tests made by amateur athletes are presented to explain the possibilities of applications of such device in research and boxers training.